2013
DOI: 10.1039/c3an36798c
|View full text |Cite
|
Sign up to set email alerts
|

Protein amyloids develop an intrinsic fluorescence signature during aggregation

Abstract: We report observations of an intrinsic fluorescence in the visible range, which develops during the aggregation of a range of polypeptides, including the disease-related human peptides amyloid-β(1-40) and (1-42), lysozyme and tau. Characteristic fluorescence properties such as the emission lifetime and spectra were determined experimentally. This intrinsic fluorescence is independent of the presence of aromatic side-chain residues within the polypeptide structure. Rather, it appears to result from electronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
230
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(254 citation statements)
references
References 37 publications
23
230
1
Order By: Relevance
“…Recently, protein fibrils have been found to absorb light in the near-UV range and to emit a structure-specific intrinsic fluorescence in the visible range even in the absence of aromatic amino acids. Most strikingly, this intrinsic visible fluorescence has been characterized to originate from the hydrogen-bonding network of protein fibrils with cross-β structures (Chan et al 2013;Lim et al 2016a;Lu et al 2016;Pinotsi et al 2016). Based on previous studies by us and other groups, a diagnostic probe of this novel intrinsic visible fluorescence can be established which is able to distinguish two different types of the fibril structures.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, protein fibrils have been found to absorb light in the near-UV range and to emit a structure-specific intrinsic fluorescence in the visible range even in the absence of aromatic amino acids. Most strikingly, this intrinsic visible fluorescence has been characterized to originate from the hydrogen-bonding network of protein fibrils with cross-β structures (Chan et al 2013;Lim et al 2016a;Lu et al 2016;Pinotsi et al 2016). Based on previous studies by us and other groups, a diagnostic probe of this novel intrinsic visible fluorescence can be established which is able to distinguish two different types of the fibril structures.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 96%
“…On the other hand, under some conditions, like the yeast prion proteins (Shorter and Lindquist 2005;Michelitsch and Weissman 2000;Chien and Weissman 2001), the TDP-43 and FUS prion-like domains have been biophysically characterized to form fibril/hydrogel structures with cross-β structures (Han et al 2012;Lim et al 2016a;Lu et al 2016;Kato and McKnight 2017;Murray et al 2017). Very unexpectedly, we discovered that the self-assembly of both TDP-43 and FUS prion-like domains into the fibril structures is highly pHdependent (Lim et al 2016a;Lu et al 2016): at low pH such as 4.0, they remained mostly monomeric for many weeks, while at neutral pH they showed a strong capacity to selfassemble into fibrils with cross-β structures as reflected by the development of intrinsic visible fluorescence, which is a novel protein fluorescence originating from the hydrogenbonding network in β-rich secondary structures (Shukla et al 2004;Chan et al 2013;Lim et al 2016a;Lu et al 2016;Pinotsi et al 2016). Furthermore, as indicated by low NMR temperature coefficients of most backbone amides, we found that, despite being intrinsically disordered, the TDP-43 prion-like domain contains a large number of intra-molecular hydrogen bonds between side chains of Ser, Thr, Asn, Gln and backbone atoms (I of Fig.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 99%
See 2 more Smart Citations
“…An intriguing phenomenon recently discovered by us is that the formation of amyloid fibrils is accompanied by the adoption of a structure specific intrinsic fluorescence in the visible range, independent of the presence of aromatic residues in the polypeptide chain 10 , 11 . This provides for a new tool in the diagnostics of aggregation kinetics in vitro and has been used as a quantitative assay, for example, to study the elongation reactions of α-synuclein 12 , see Figure 2.…”
Section: Bulk Measurements To Study Fibril Growthmentioning
confidence: 99%